Reduced wear in vitamin E-infused highly cross-linked polyethylene cups: 5-year results of a randomized controlled trial. (4th March 2021) - Rochcongar, Goulven; Remazeilles, Matthieu; Bourroux, Emeline; Dunet, Julien; Chapus, Valentin; Feron, Matthieu; Praz, César; Buia, Geoffrey; Hulet, Christophe
Abstract : Background and purpose — Vitamin E-infused polyethylene is a relatively new material in joint arthroplasty; there are no long-term reports, and only few mid-term results. Using radiostereometric analysis (RSA), we primarily determined whether vitamin E-infused highly cross-linked polyethylene (HXLPE/VitE) acetabular cups show less wear than ultra-high molecular weight polyethylene (UHMWPE) acetabular cups at 5 years after total hip arthroplasty (THA). We also assessed whether wear rates correlate with increasing cup inclination angles or cup sizes. Patients and methods — This is a 5-year follow-up of our previously reported randomized controlled trial of 62 patients with 3 years' follow-up, who received THA with either an HXLPE/VitE or a UHMWPE acetabular cup. At 5 years, 40 patients were analyzed (22 in the HXLPE/VitE and 18 in the UHMWPE group). Results — HXLPE/VitE cups continued to show less cumulative femoral head penetration than UHMWPE cups (HXLPE/VitE: 0.24 mm, UHMWPE: 0.45 mm; p < 0.001). Distribution of wear was also more even with HXLPE/VitE cups than with UHMWPE cups (p = 0.002). Moreover, the difference in PE wear between 1 and 5 years in both groups showed no statistically significant correlation with increasing cup inclination angles or cup sizes. Finally, no osteolysis and implant loosening occurred, and no revision surgeries were required. Interpretation — Wear rates continue to be lower in HXLPE/VitE cups than in UHMWPE cups at 5 years of follow-up without correlation with increasing cup inclination angles or cup sizes. Finally, HXLPE/VitE cups may have the potential to prevent osteolysis and implant loosening.